Adopsi Inovasi Teknologi Pengolahan Biobriket Tongkol Jagung Sebagai Sumber Energi Baru Terbarukan Pada Masyarakat Hutan - Ashlihah Ashlihah; Purbowo Purbowo; Dyah Ayu Sri Hartanti (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2024)
Indonesia's dependence on fossil energy is caused by the lack of consistency in renewable energy design and legal political targets. A sustainable energy transition through decarbonizing power plants uses renewable energy sources such as biomass, solar, hydro, nuclear and geothermal energy. This research aims to determine the level of community participation before and after participating in training on corncob bio briquette processing technology. The research was conducted in Asemgede village which is located in the middle of the forest and is the boundary between Jombang and Lamongan districts. Respondents are people who work as charcoal craftsmen as well as corn farmers. Data was collected before and after the training program by distributing pre and post test questions. There are two estimation hypotheses, namely that there is a significant difference and there is no significant difference between before and after the program. The data analysis method uses a paired T test (comparison). The research results show that there are significant differences between before and after the empowerment program. The average score during the participants' pre-test was 3, which means it was very limited, but after the program was implemented the average score was 7, which means the participants were proficient in knowledge and skills in bio briquette processing technology. A sustainable assistance program is needed to establish the legality of micro/small business institutions and product certification so that they can carry out production and meet domestic energy needs.